2017
DOI: 10.1007/s00276-017-1837-8
|View full text |Cite
|
Sign up to set email alerts
|

Immobile cerebral veins in the context of positional brain shift: an undescribed risk factor for acute subdural hemorrhage

Abstract: The parasagittal major cortical and bridging veins do not seem to show positional shifts. Positional change in the posterior-anterior direction causes a shearing between the frontal cortices and the distributing veins and can be a risk factor for acute subdural hemorrhage, in case of severe head trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Previous studies using conventional horizontal imaging have reported postural brain displacements in supine versus prone or lateral positions 15 17 , whereas until recently, only few studies have evaluated intracranial positional shifts in supine versus upright posture. Although early mobilization is recommended after surgeries, safety during mobilization has not been completely validated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using conventional horizontal imaging have reported postural brain displacements in supine versus prone or lateral positions 15 17 , whereas until recently, only few studies have evaluated intracranial positional shifts in supine versus upright posture. Although early mobilization is recommended after surgeries, safety during mobilization has not been completely validated.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with a large volume of residual intracranial air, rapid postural changes should be prevented, and possible stretching of the frontoparietal bridging veins while in upright position, which is not expected from examinations performed in supine position, must be considered. A study of PBS evaluated via supine versus prone MRI performed a similar assessment of the risk of bridging vein damage caused by positional change 17 . Major cortical and bridging veins do not show positional shifts compared with brain parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Greater deformation could be seen further away from anatomical boundaries, and in particular in deeper structures, such as T, BG and BStem, confirming the influence of both gravity and anatomical constraints reported in the literature. The joint effect of the curved shape of the skull and the anchoring effect of the BStem most likely induced the anticlock-wise rotation around the L–R axis 1 , 2 , 53 ; simultaneously, the tethering effect created by the meningeal and vascular elements might have contributed to the smaller deformation near these cortical areas 26 , 27 , 54 . The falx cerebri most likely limited any shift along its surface, inhibiting any deformation along the L–R direction (in particular at the level of the WM) 1 , 2 ; Finally, the tentorium cerebelli reduced the I–S deformation of the lowermost part of cerebrum.…”
Section: Discussionmentioning
confidence: 99%
“…Greater deformation could be seen further away from anatomical boundaries, and in particular in deeper structures, such as T, BG and BStem, confirming the influence of both gravity and anatomical constraints reported in the literature. The joint effect of the curved shape of the skull and the anchoring effect of the BStem most likely induced the anticlock-wise rotation around the L-R axis 1,2,53 ; simultaneously, the tethering effect created by the meningeal and vascular elements might have contributed to the smaller deformation near these cortical areas 26,27,54 . The falx cerebri most likely limited any shift along its surface, inhibiting any deformation along the L-R direction (in particular at the level of the WM) 1, 2 ; Finally, the tentorium cerebelli reduced the I-S deformation of the lowermost part of cerebrum.…”
Section: Discussionmentioning
confidence: 99%